The effectiveness of game-based learning using Wayground on students' interest and performance in English at an Indonesian junior high school - Wiwintisari Mahis; Harmita Sari; Rusandi; Ming Chou Liu (JEELS (Journal of English Education and Linguistics Studies), 2026)
Although digital platforms and gamification are increasingly used in English language classrooms, maintaining students’ interest and performance in learning remains a challenge. Therefore, this study examines whether the use of Wayground online teaching media affects students' interest and performance in English language learning, with student feedback and ease of teaching material as mediating variables. A quantitative approach was applied using an online questionnaire with a five-point Likert scale as the research instrument. Data were collected through random practical sampling from 142 junior high school students with experience using Wayground. The data were then analyzed using Structural Equation Modelling (SEM) with AMOS and SPSS version 25.  The results show that the use of Wayground online teaching media has a significant positive effect on student interest (coefficient = 0.200; p < 0.01). However, the use of Wayground online teaching media does not directly affect students’ learning performance (coefficient = 0.029; non-significant). In addition, student feedback and ease of teaching materials were found to be highly significant mediating variables in the relationship between the use of Wayground online teaching media and student performance (p < 0.001). These findings suggest that effective digital English learning requires system usability, meaningful interactions, quality feedback, and relevant materials. Research on Wayground media highlights these elements as vital for future educational success.